Case Report: Extra skeletal Ewing’s sarcoma of mediastinum: clinical experience and literature review - Hu, Xianwen; Zhao, Wei; Yu, Ronghua; Pan, Dongfeng (Frontiers in Oncology, 2025)
Extraskeletal Ewing sarcoma (EES) is a malignant tumor that arises in soft tissues outside the skeleton. It commonly involves the paravertebral regions, the lower extremities, and the chest wall, with mediastinal involvement being less frequent. Here, we report an 11-year-old male with pathologically confirmed EES occurring in the mediastinum. Chest computed tomography (CT) showed a large soft tissue density mass on his left posterior mediastinum, containing internal low-density cystic necrotic areas. The solid component was isointense to muscle on T1-weighted imaging (T1WI) and mildly hyperintense on T2-weighted imaging (T2WI), whereas the cystic components were hyperintense on T2WI and variably hyperintense on T1WI. On contrast-enhanced CT and T1WI, the mass demonstrated heterogeneous, progressive enhancement, suggesting the possibility of malignant tumor. A needle biopsy confirmed the diagnosis of EES. After diagnosis, the patient received systemic chemotherapy followed by surgical resection of the tumor. We also conducted a systematic review of the published literature on mediastinal EES, summarizing its clinical and imaging features, with the aim of increasing understanding of this rare disease.